RADBIOMOD: A simple program for utilising biological modelling in radiotherapy plan evaluation. Issue 1 (January 2016) - Chang, Joe H.; Gehrke, Christopher; Prabhakar, Ramachandran; Gill, Suki; Wada, Morikatsu; Lim Joon, Daryl; Khoo, Vincent
Highlights: A simple program, RADBIOMOD, has been developed for radiobiological plan evaluation. Multiple radiobiological models in RADBIOMOD were compared with existing software. Calculations in RADBIOMOD closely matched those from other modelling software. Abstract: Purpose: Radiotherapy plan evaluation is currently performed by assessing physical parameters, which has many limitations. Biological modelling can potentially allow plan evaluation that is more reflective of clinical outcomes, however further research is required into this field before it can be used clinically. Methods: A simple program, RADBIOMOD, has been developed using Visual Basic for Applications (VBA) for Microsoft Excel that incorporates multiple different biological models for radiotherapy plan evaluation, including modified Poisson tumour control probability (TCP), modified Zaider–Minerbo TCP, Lyman–Kutcher–Burman normal tissue complication probability (NTCP), equivalent uniform dose (EUD), EUD-based TCP, EUD-based NTCP, and uncomplicated tumour control probability (UTCP). RADBIOMOD was compared to existing biological modelling calculators for 15 sample cases. Results: Comparing RADBIOMOD to the existing biological modelling calculators, all models tested had mean absolute errors and root mean square errors less than 1%. Conclusions: RADBIOMOD produces results that are non-significantly different from existing biological modelling calculators for the models tested. It is hoped that this freely available, user-friendly program will aid future research into biological modelling.